Molecular characterization and inhibition of amanitin uptake into human hepatocytes - Letschert, Katrin; Keppler, Dietrich (Toxicological sciences, 2006)
Amatoxins are the main poison of the green death cap (Amanita phalloides) and among the most dangerous natural toxins causing hepatic failure. A possible therapeutic approach is the inhibition of the transporting systems mediating the uptake of amatoxins into human hepatocytes, which, however, have yet to be identified. In the current study we tested whether members of the organic anion-transporting polypeptide (OATP) family, localized in the sinusoidal membranes of human hepatocytes, are involved in amatoxin uptake. For this, Madin Darby canine kidney strain II (MDCKII) cells stably expressing human OATP1B3, OATP2B1, or OATP1B1, were assayed for the uptake of 3H-labeled O-methyl-dehydroxymethyl-α-amanitin. Under our conditions, only OATP1B3 was able to transport amanitin with a Km value of 3.7μM ± 0.6μM. Accordingly, toxin uptake was inhibited by OATP1B3 substrates and inhibitors (cyclosporin A, rifampicin, the quinoline derivatives MK571 ([(3-(3-(2-(7-chloro-2-quinolinyl)ethenyl)phenyl)((3-dimethylamino-3-oxopropyl)thio)methyl)thiopropanoic acid]) and montelukast, the cholecystokinin octapeptide (CCK-8), paclitaxel, and bromosulfophthalein), as well as by some antidotes used in the past for the treatment of human amatoxin poisoning (silibinin dihemisuccinate, penicillin G, prednisolone phosphate, and antamanide). These transport studies are in line with viability assays monitoring the toxic effect of amanitin on the transfected MDCKII cells. Further support for amatoxin transport was found in primary human hepatocytes, expressing OATP1B3, OATP2B1, and OATP1B1, where CCK-8, a substrate specific for OATP1B3, prevented the fragmentation of nucleoli, a lesion typical for amanitin action. In conclusion, we have identified OATP1B3 as the human hepatic uptake transporter for amatoxins; moreover, substrates and inhibitors of OATP1B3, among others rifampicin, may be useful for the treatment of human amatoxin poisoning.
Gesehen am 18.02.2021